Baseline neutrophil-to- ratio combined with the change during treatment provides risk stratification for metastatic malignant melanoma patients treated with PD-1 inhibitors in a Chinese population - Wang, Chen; Liu, Shengyan; Li, Xin; Cui, Kang; Zhang, Weijie; Du, Yabing (Frontiers in Oncology, 2023)
Background: Previous studies have suggested that an elevated baseline neutrophil-to-lymphocyte ratio (BLNLR) and elevated relative change of NLR (∆NLR%) is associated with worse outcomes in patients with a variety of cancers. This study is aim to investigate the value of BLNLR and ∆NLR% before the third cycle of treatment on the prognosis of patients with metastatic malignant melanoma treated with PD-1 inhibitors. Methods: A total of 63 patients with metastatic malignant melanoma treated with PD-1 inhibitors in the First Affiliated Hospital of Zhengzhou University from January 2017 to December 2021 were retrospectively analyzed. BLNLR and ∆NLR% before the third cycle of treatment were collected. The Kaplan-Meier method was used to draw survival curves and Log-Rank test was used for survival analysis. Univariate and multivariate Cox regression analysis were used to analyze the relationship between BLNLR, ∆NLR% and clinical characteristics with progression-free survival (PFS) and overall survival (OS). Results: Univariate analysis showed that PFS and OS were associated with BLNLR, ∆NLR%, BMI and number of metastatic organs (P < 0.05). Multivariate analysis showed that BLNLR, ∆NLR%, BMI and number of metastatic organs were independent predictors of OS, and BLNLR and ∆NLR% were independent predictors of PFS. Patients were divided into four groups according to BLNLR (<3, ≥3) and ∆NLR% (< 30%, ≥30%): low-BLNLR and low-∆NLR% group, low-BLNLR and high-∆NLR% group, high-BLNLR and low-∆NLR% group, high-BLNLR and high-∆NLR% group. The median OS was 20 months, 8 months, 9 months, 5 months and the median PFS was 8 months, 3 months, 2 months, 2 months, respectively. Conclusion: BLNLR combined with ∆NLR% can be used to predict the prognosis of PD-1 inhibitors in patients with metastatic malignant melanoma.